Einstein aujourd'hui - Aspect, Alain (Savoirs actuels. Physique., 2005)
The objective of this book is to demonstrate how alive and inspiring Einstein's ideas still are in the scientific domain at the onset of the 21st century. It includes seven contributions: an introduction which deals with the historical dimension and six articles that scan Einstein's most important works and their impact on today's physics.